2009
DOI: 10.1212/wnl.0b013e3181c33adf
|View full text |Cite
|
Sign up to set email alerts
|

Intensive coordinative training improves motor performance in degenerative cerebellar disease

Abstract: This study provides Class III evidence that coordinative training improves motor performance and reduces ataxia symptoms in patients with progressive cerebellar ataxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
249
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(279 citation statements)
references
References 28 publications
14
249
0
16
Order By: Relevance
“…Although several postural parameters correlated with the severity of the disease, no significant changes in ataxia scores over time were observed. Both Ilg et al (2009) andMiyai et al (2012) identified earlier a significant improvement in clinical ataxia scores, most likely because their coordinative training included tasks that more closely resemble items assessed in the ataxia scales ICARS and SARA (Trouillas et al, 1997;Schmitz-Hübsch et al, 2006).…”
Section: Training-related Postural Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several postural parameters correlated with the severity of the disease, no significant changes in ataxia scores over time were observed. Both Ilg et al (2009) andMiyai et al (2012) identified earlier a significant improvement in clinical ataxia scores, most likely because their coordinative training included tasks that more closely resemble items assessed in the ataxia scales ICARS and SARA (Trouillas et al, 1997;Schmitz-Hübsch et al, 2006).…”
Section: Training-related Postural Changesmentioning
confidence: 99%
“…Yet, only recently, three well controlled group studies have demonstrated significant motor benefit following coordinative training. Ilg et al (2009Ilg et al ( , 2010 reported that after a 4 week intensive coordinative training cerebellar patients improved motor performance, reduced their ataxic symptoms, and sustained these benefits for up to one year. Similar gains persisting for 6 months following a 1 month rehabilitation program were also shown by Miyai et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Resultaram um total de 13 artigos, sendo 4 revisões da literatura 13,18,19,20 , 5 estudos de caso 9,15,21,22,23 e 4 ensaios clínicos 11,14,24,25 . Os tipos de estudo, procedimentos realizados e principais resultados apresentados naqueles que envolviam métodos de atendimento fisioterapêutico estão apresentados na Tabela 1.…”
Section: Resultsunclassified
“…A marcha pode ficar atáxica, com ampliação da base de sustentação, instabilidade, passos irregulares e mais lentos, lateropulsão e tremor na amplitude de movimento 11 .…”
Section: Introductionunclassified
“…Six RCTs [2, [49][50][51][52][53][54] were included in these systematic reviews that were published before October 2016. In addition, another RCT [55] was found in PubMed, upon searching for all systematic reviews and RCT reports regarding physical therapy that were published from 1980 to 2016.…”
Section: Reviewmentioning
confidence: 99%